PTU-102 Development Of A Food Related Quality Of Life Questionnaire For People With Ibd. (9th June 2014) - Hughes, L; Lindsay, JO; Lomer, MC; Ayis, S; King, L; Morgan, M; Whelan, K
Abstract : Introduction: The role of diet as a therapy for Inflammatory Bowel Disease (IBD) is well established and has improved treatment and prognosis for patients. However, little is understood about how IBD impacts on food-related quality of life. A qualitative study indicated a wide range of food related issues across a broad spectrum of IBD experiences which include, amongst others; identifying and avoiding trigger foods, uncertainty about eating and drinking, problems eating out and frustration around eating. This study aimed to develop a food-related quality of life (FRQoL) questionnaire for people with IBD. Methods: Semi-structured interviews with 28 IBD patients were coded and 150 FRQoL questionnaire items were generated. One hundred IBD patients ranked each item on i) if it had been relevant to them in the past two weeks and; 2) how important it was to them (regardless of whether it had been relevant). Items were removed based on ceiling/floor effects and high inter-item correlations. The 41 highest ranking items were retained with a 5 point Likert (disagree-agree) response scale. Subsequently, 287 IBD patients, 100 asthma patients (chronic disease control) and 117 healthy volunteers completed the FRQoL questionnaire alongside clinical measures, MUST nutritional screening, food satisfaction and generic and disease-specific quality of life questionnaires. Psychometric testing of the FRQoL questionnaire has been carried out including principle components analysis, construct and discriminant validity and test-retest reliability. Results: Initial principle components analysis identified seven components explaining 68.35% of variance with high internal reliability (Cronbach's alpha = 0.96). The FRQoL sumscore (higher scores indicate worse quality of life) correlated with younger age (r = -0.12), higher MUST score (r = 0.17) and lower BMI (r = -0.13). Worse FRQoL was associated with female gender (p < 0.001), a diagnosis of Crohn's Disease (p < 0.05), surgery (p < 0.05) and high MUST score (p < 0.05). Conclusion: An FRQoL questionnaire has been developed to identify issues around food, eating and nutrition for people with IBD at all stages of the disease process. Preliminary psychometric testing indicates that the questionnaire sumscore is related to clinical characteristics indicative of poor FRQoL. Further testing will determine the validity and reliability of the questionnaire for clinical use to identify IBD patients who may require further support with eating and drinking. Disclosure of Interest: None Declared.